Strategi Penguasaan Materi Ajar dalam Perkuliahan Microteaching pada Mahasiswa Program Studi Pendidikan Guru Sekolah Dasar - Elviana Seran; Roswita Luruk Klau; Maria Yunita Nahak; Theresia S.S Mendez; Fridolin R Lalu; Magdalena Eka; Viktoria A Buik; Damian Puling; Augusta D.J.Magalhaes (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Microteaching is an essential component in preparing students of the Primary School Teacher Education (PGSD) program to become competent professional educators. This study aims to analyze effective strategies for mastering teaching materials during microteaching courses for PGSD students. Optimal mastery of subject matter requires not only a deep understanding of content but also the ability to adapt to the characteristics of primary school students, the use of varied teaching methods, and effective communication skills. This study employs a literature review methodology and analyzes best practices from various educational institutions. The results indicate that strategies for mastering teaching materials in microteaching involve five key dimensions: systematic material preparation through curriculum analysis and in-depth literature study; material organization using a logically structured approach; material presentation with diverse learning models and appropriate media; continuous evaluation using assessment for learning techniques; and self-development through continuous learning and consistent practice. The implementation of this integrated strategy has been proven to increase student confidence, improve the quality of material delivery, and optimize teaching readiness in primary school settings. These findings offer significant contributions to the development of PGSD curricula and the enhancement of the quality of future primary school teachers in Indonesia.